2021
DOI: 10.1177/15570851211062572
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment of Students at Institutions of Higher Education: Variations in Students’ Experiences, Knowledge, and Perceptions Across Institutions

Abstract: Attention to sexual misconduct has focused on acquaintance rape, leaving a need for research on less highly recognizable forms of harm. We estimated institution of higher education (IHE)-specific prevalence of yellow zone sexual harassment (SH) among students at 27 IHEs. We then examined SH and perceived risk of sexual assault/misconduct, knowledge regarding policies/resources, and perceptions of sexual misconduct response. Between 37.1% and 55.7% of students experienced SH. Harassed students were much more li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…These findings are consistent with previous studies (e.g., Richards et al, 2021b), and underscore the need to critically examine whether the current Title IX processes—including mandatory reporting—are serving survivors and the overall campus climate. Indeed, the limited prior research on survivors’ experiences with reporting to Title IX as well as the Title IX investigation and disciplinary process notes overwhelmingly negative experiences (Holland & Cipriano, 2021; Cipriano et al, 2021) and high personal “costs” of reporting for survivors (e.g., retaliation, shame, disbelief; Know Your IX, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous studies (e.g., Richards et al, 2021b), and underscore the need to critically examine whether the current Title IX processes—including mandatory reporting—are serving survivors and the overall campus climate. Indeed, the limited prior research on survivors’ experiences with reporting to Title IX as well as the Title IX investigation and disciplinary process notes overwhelmingly negative experiences (Holland & Cipriano, 2021; Cipriano et al, 2021) and high personal “costs” of reporting for survivors (e.g., retaliation, shame, disbelief; Know Your IX, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of 10 articles by Klein and Martin (2019) found that estimates of sexual harassment of U.S. college students vary widely across studies in the published literature using different sampling techniques and methods, from 9% (Campbell et al, 2021) to 97% (Yoon et al, 2010). Additional analysis of survey data from nearly 147,000 undergraduate, graduate, and professional students at 27 U.S. IHEs found that 37–56% of students reported experiencing sexual harassment since entering the IHE (Klein et al, 2022).…”
Section: Sexual Harassment Of Us College Studentsmentioning
confidence: 99%
“…Regarding perpetrators of sexual harassment against college students, studies show that while most undergraduate students report being harassed by a fellow undergraduate or graduate student (Klein & Martin, 2019; Klein et al, 2022), both undergraduate and graduate students report sexual harassment from faculty, and graduate students report that faculty are the primary perpetrators of their harassment (Klein & Martin, 2019). While prior research on sexual harassment among U.S. college students outside of 4-year schools is limited, a campus climate assessment of seven community colleges in New Hampshire found that 19% of students reported sexual harassment by a faculty/staff member (Howard, 2019).…”
Section: Sexual Harassment Of Us College Studentsmentioning
confidence: 99%
See 2 more Smart Citations